2020
DOI: 10.7150/jca.46547
|View full text |Cite
|
Sign up to set email alerts
|

Wnt5a regulates Ameloblastoma Cell Migration by modulating Mitochondrial and Cytoskeletal Dynamics

Abstract: Objective: Abnormal expression of Wnt5a has been detected in various tumors, including ameloblastoma (AB). Yet, there is no specific mechanistic evidence for the functional role of Wnt5a in AB. In this study, we aimed to conduct a mechanistic examination of the importance of Wnt5a in AB development. Methods: The expressions of Wnt5a and Coro1A were examined by Western blot and immunohistochemistry both in AB tissues and AM-1 cells. The number and size of mitochondria were detected by electronic transmission mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Previous research has demonstrated that Sal B may restrain the migration and invasion of hepatocellular carcinoma through RECK/STAT3 signaling [ 28 ]. For crossing the basement membrane along with the basal layer, tumor cells are functionally and morphologically altered through activating EMT that has the features of upregulation of β -cadherin and downregulation of E-cadherin [ 29 ]. Sal B administration enabled the decrease β -cadherin expression as well as the enhancement of E-cadherin expression of NCI-H2030 and NCI-H1650 cells, demonstrating the inactivation of EMT in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that Sal B may restrain the migration and invasion of hepatocellular carcinoma through RECK/STAT3 signaling [ 28 ]. For crossing the basement membrane along with the basal layer, tumor cells are functionally and morphologically altered through activating EMT that has the features of upregulation of β -cadherin and downregulation of E-cadherin [ 29 ]. Sal B administration enabled the decrease β -cadherin expression as well as the enhancement of E-cadherin expression of NCI-H2030 and NCI-H1650 cells, demonstrating the inactivation of EMT in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…These phenomena are consistent with the pathological finding of ameloblastoma cells invading the stroma and bone, similar to tuft formation. Recently, BRAF and Wnt signals were reported to contribute to the cell proliferation and migration of ameloblastoma cells, respectively 33–35 . Our findings suggested that IL‐1α might be the novel therapeutic target of ameloblastoma in addition to these molecules.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, BRAF and Wnt signals were reported to contribute to the cell proliferation and migration of ameloblastoma cells, respectively. [33][34][35] Our findings suggested that IL-1α might be the novel therapeutic target of ameloblastoma in addition to these molecules.…”
Section: Discussionmentioning
confidence: 67%
“…3,43,44 Migration and invasion of tumor cells represent two crucial biological phenomena during metastases. 45,46 Herein, loss of TRIM11 decreased the migratory and invasive capacities of prostate cancer cells. In line with our experimental data, several researchers have determined that TRIM11 is correlated to migration and invasion in several human cancers.…”
Section: Discussionmentioning
confidence: 97%